EMPOWERING LOCAL FARMERS THROUGH SUSTAINABLE CEMPEDAK PROCESSING AND MARKETING: A CASE STUDY OF KO YO AMPHOE SONGKLA, THAILAND - Darmawan, Fery; Rinunate, Cacak; Fitriyani; Diana, Asri; Faiziah, Anita; Farlian, Talbani; Suriani, Suriani; Sartiyah, Sartiyah (RADJA PUBLIKA, 2025)
Ahsan, D., Brandt, U. S., & Faruque, H. (2021). Local agricultural practices to adapt with climate change. Is sustainability a priority? Current Research in Environmental Sustainability, 3. https://doi.org/10.1016/j.crsust.2021.100065 Catur Rahayu Martiningtiyas, Hermawan, A., Chaniago, N., Baliartati, B. O., & Lestari, N. (2022). Peran Media Sosial untuk Pemasaran Digital. Dirkantara Indonesia, 1(1), 25–30. https://doi.org/10.55837/di.v1i1.30 Fitriyani, A., Safitri, D. M., Ustin, N. A., & Dewi, Y. P. (2024). Pengembangan Strategi Pemasaran Berkelanjutan untuk Produk Ramah Lingkungan: Literature Review. Jurnal Disrupsi Bisnis, 7(1), 101–110. https://doi.org/10.32493/drb.v7i1.35412 Gumbi, N., Gumbi, L., & Twinomurinzi, H. (2023). Towards Sustainable Digital Agriculture for Smallholder Farmers: A Systematic Literature Review. In Sustainability (Switzerland) (Vol. 15, Issue 16). Multidisciplinary Digital Publishing Institute (MDPI). https://doi.org/10.3390/su151612530 Mahrinasari, M. S., Bangsawan, S., & Sabri, M. F. (2024). Local wisdom and Government’s role in strengthening the sustainable competitive advantage of creative industries. Heliyon, 10(10). https://doi.org/10.1016/j.heliyon.2024.e31133 Pui, L. P., Karim, R., Yusof, Y. A., Wong, C. W., & Ghazali, H. M. (2020). Optimization of spray-drying parameters for the production of ‘Cempedak’ (Artocarpus integer) fruit powder. Journal of Food Measurement and Characterization, 14(6), 3238–3249. https://doi.org/10.1007/s11694-020-00565-3 Rachmawati, R. R. (2021). Smart Farming 4.0 Untuk Mewujudkan Pertanian Indonesia Maju, Mandiri, Dan Modern. Forum Penelitian Agro Ekonomi, 38(2), 137. https://doi.org/10.21082/fae.v38n2.2020.137-154 Saiyut, P., Bunyasiri, I., Sirisupluxana, P., & Mahathanaseth, I. (2017). Changing age structure and input substitutability in the Thai agricultural sector. Kasetsart Journal of Social Sciences, 38(3), 259–263. https://doi.org/10.1016/j.kjss.2016.07.004 Yang, C., Ji, X., Cheng, C., Liao, S., Obuobi, B., & Zhang, Y. (2024). Digital economy empowers sustainable agriculture: Implications for farmers’ adoption of ecological agricultural technologies. Ecological Indicators, 159. https://doi.org/10.1016/j.ecolind.2024.111723 Yudianto, A., Studi, P., Bisnis, A., Tinggi, S., & Amuntai, I. A. (2024). Peningkatan Ekonomi Melalui Pengolahan Kulit Buah Cempedak Dalam Pengabdian Masyarakat Di Desa Kota Raden, Kec. Amuntai Tengah, Kab. Hulu Sungai Utara. In Communnity Development Journal (Vol. 5, Issue 4).